Susceptibility of provenances of spotted gums to Ramularia shoot blight - Self, N.M.; Aitken, E.A.B.; Dale, M.D. (New Zealand Plant Protection, 2002)
Shoot blight of spotted gums (Eucalyptus maculata Hook E citriodora Hook and E henryi ST Blake) caused by Ramularia pitereka Unger has recently emerged as the major disease problem of spotted gum plantations in Queensland and Northern New South Wales A difference in disease susceptibility was demonstrated between provenances of spotted gums inoculated with Ramularia spores under field conditions A number of other Eucalyptus species inoculated with Ramularia showed no susceptibility The potential for breeding from resistant provenances and for creating resistant hybrids using crosses with resistant species such as Eucalyptus torelliana FMuell is discussed